ANALISIS PENGENDALIAN MUTU FISIK STRUKTUR PADA PROYEK PEMBANGUNAN GEDUNG PENDIDIKAN SBSN KAMPUS III UIN IMAM BONJOL PADANG - Jatira Jasmaranti; M Giatman (Jurnal Applied Science in Civil Engineering, 2022)
: The structure of the building is a major part of a building. Quality planning of building structures must be planned and implemented according to standards, both in terms of strength quality standards and in terms of building physical quality standards. So this study was conducted with the aim of (1) Knowing the factors that cause deviations in the physical quality of the column and beam structure in the SBSN Education Building Construction project Campus III UIN Imam Bonjol Padang, (2) Knowing the control of deviations in the physical quality of the column and beam structure work in the Building Construction project. SBSN Education Campus III UIN Imam Bonjol Padang. This type of research is a quantitative research with a descriptive approach. The research instrument is a questionnaire/questionnaire. The instrument validation was tested by expert judgment and then the questionnaire instrument was tested. The results showed that there are 5 factors that cause deviations in the quality of the column and beam structures included in the influential category. The results of data analysis that have been carried out show that (1) human resource factors are included in the influential category with a DP value of 81.95%, (2) material factors are included in the influential category with a DP value of 85.33%, (3 ) the equipment factor is included in the influential category with a DP value of 87.17%, (4) the work procedure factor is included in the influential category with a DP value of 89.08%, (5) the work implementation factor is included in the influential category with a DP value of 89 ,83%.